2012
DOI: 10.1186/1472-6882-12-173
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and anti-inflammatory activities of selected Chinese medicinal plants and their relation with antioxidant content

Abstract: BackgroundThe main aim of this study is to evaluate the antioxidant and anti-inflammatory properties of forty four traditional Chinese medicinal herbal extracts and to examine these activities in relation to their antioxidant content.MethodsThe antioxidant activities were investigated using DPPH radical scavenging method and yeast model. The anti-inflammatory properties of the herbal extracts were evaluated by measuring their ability to inhibit the production of nitric oxide and TNF-α in RAW 264.7 macrophages … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
182
1
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 251 publications
(199 citation statements)
references
References 57 publications
10
182
1
6
Order By: Relevance
“…In fact, several previous works described the importance of the biological functions of these molecules such as antioxidant 24,[30][31][32] , anti-inflammatory 33,34 , anti-atherosclerotic 35,36 , anticancer 35,37,38 and antimicrobial activities 39,40. Indeed, the ethanol-ethyl acetate (2/1) extract contains 28 mg GAE/g DW of phenolic compounds and 7 mg EQ/g DW of flavonoid contents and show an impor-1 tant antioxidant activity measured on DPPH with an IC50 of 42 µg/mL. These results are in agreement with those obtained by 41 and 24 who reported that there is a close relationship between phenolic and flavonoid content and the antioxidant activity in Eriobotrya japonica extracts.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, several previous works described the importance of the biological functions of these molecules such as antioxidant 24,[30][31][32] , anti-inflammatory 33,34 , anti-atherosclerotic 35,36 , anticancer 35,37,38 and antimicrobial activities 39,40. Indeed, the ethanol-ethyl acetate (2/1) extract contains 28 mg GAE/g DW of phenolic compounds and 7 mg EQ/g DW of flavonoid contents and show an impor-1 tant antioxidant activity measured on DPPH with an IC50 of 42 µg/mL. These results are in agreement with those obtained by 41 and 24 who reported that there is a close relationship between phenolic and flavonoid content and the antioxidant activity in Eriobotrya japonica extracts.…”
Section: Discussionmentioning
confidence: 99%
“…Large amounts of reactive oxygen species accumulate in the aqueous fluid and lenses with age; they cause SOD and GSH-PX consumption, changing the soluble proteins in the lens into insoluble proteins, which results in lens opacity (Lu and Rasco, 2012;Gupta and Ahmad, 2013). Reduced CAT weakens the antioxidant capacity of the lens epithelial cells and induces their apoptosis, which also causes cataracts (Ravipati et al, 2012;Zhu et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Antioxidant activity screening was done in a 96-well microplate high throughput assay using Saccharomyces cerevisiae as described before 18,20 . Briefly, S. cerevisiae (BY4743) were cultured overnight then diluted to an optical density of 0.2 at 600 nm (OD600) in the media.…”
Section: Yeast-based Antioxidant Screening Assaymentioning
confidence: 99%